Integrating religious values in counselling Muslim gay students: the experiences of Muslim counselors - Syed Mahmood, Syarifah Rohaniah; Ssekamanya, Siraje Abdallah (Seminar Kebangsaan Majlis Dekan Pendidikan Universiti Awam Malaysia, 2019)
A phenomenological method of qualitative inquiry was used to explain how Muslim counsellors integrate religious values in counselling Muslim gay students. In-depth interviews were conducted with six Muslim counsellors at Public Institutions of Higher Education (PIHE) in Peninsular Malaysia. The findings revealed that the Muslim counsellors used six strategies in integrating religious values: emphasis on “ibadah”, guide clients to think of “hikmah”, ask provocative questions, explain religious views, emphasis on good relationship with parents and give suggestions. They integrate religious values in their counselling sessions to give insights and bring positive changes to the students.